Past Trends and Future Projections of Climate and Hydrology over Asia including 18 Demonstration Basins in Asian Water Cycle Initiative (AWCI) Countries - Bae, D.; Koike, Toshio; Lee, Moon-Hwan (APN Science Bulletin, 2014)
The present study analysed historical climate and hydrology trends of future climate change impacts over 18 demonstration basins in Asian Water Cycle Initiative (AWCI) countries. The Mann-Kendall test was employed for past trend analyses. The analysis showed an increasing trend for average temperature and a decreasing trend for average precipitation and runoff over Asia in the past 30 years (1977–2006). To analyse future climate change impacts, three Global Circulation Models (GCMs), i.e., CGCM3_T47, CGCM2_3_2 and CM4 were selected using criteria based on probabi listic uncertainty analysis, correlation coefficient and RMSE. The analysis projected increases in average temperature, precipitation and runoff over Asia in 2020s, 2050s and 2080s. By 2080s, the average temperature, precipitation and runoff over Asia were projected to increase by 3.7°C, 10.7% and 11.1%, respectively.
Keywords: climate change; trends analysis; Mann-Kendall; GCM